Second language listening comprehension: The role of anxiety and enjoyment in listening metacognitive awareness - Wang, Lanxi; MacIntyre, Peter (Studies in Second Language Learning and Teaching, 2021)
Emotion in second language acquisition (SLA) has recently received greater attention because it is largely implicated in daily conversations, which may affect second or foreign language (L2) use including listening comprehension. Most research into emotion and L2 listening comprehension is focused exclusively on anxiety, with an attempt to reduce its negative effects on individuals’ listening performance. With the arrival of positive psychology in SLA, researchers began to take a holistic view of a wider range of emotions including enjoyment that language learners experience during their L2 communication. The current study explored the relationships among listening anxiety, enjoyment, listening comprehension performance, and listening metacognitive awareness among a group of 410 international students in a Canadian university. Correlational analyses showed that listening anxiety was negatively correlated with enjoyment. However, these two variables shared only 18% of their variance, indicating that listening anxiety and enjoyment are related but independent emotions. This study suggests that anxiety and enjoyment in L2 listening are not the opposite ends of the same emotional continuum, but each serves a different purpose. L2 learners should work to find intriguing and enjoyable experiences in language learning, rather than focusing merely on reducing anxiety.